Penegakan Hukum terhadap Pengendara Motor yang Tidak Menggunakan Helm saat Berpakaian Adat Bali di Wilayah Hukum Polres Tabanan - Ni Made Yuli Ratna Dewi; I Nyoman Putu Budiartha; I Ketut Sukadana (Jurnal Preferensi Hukum, 2020)
National integrity and development are strongly supported by the role of traffic and road transportation as a step to improve the welfare of the community. For those who ride motorbikes are required to use a helmet as a cycling equipment as stipulated in article 106 paragraph 8 of Law Number 22 Year 2009 concerning Traffic and Road Transportation. But there is a difference when someone who rides a special motorcycle wearing traditional Balinese clothes. The purpose of this research is to analyze the level of compliance of motorcycle riders in using helmets and analyze the obstacles of the police in upholding the law against violations while dressed in Balinese custom. The method used in this study is an empirical legal approach which is done by interacting directly with the object under study with a sociological and legislative approach. The technique used in collecting data is semi-structured interviews. The results of this study indicate that the level of compliance of the Tabanan community in traffic is still low because seen from data from 2016 to 2018 the number of violations tends to increase with the number of violations in 2016 as many as 1394 in 2017 as many as 1186 and in 2018 as many as 2424 violators. Even though in 2017 there has been a reduction in violations, it can still be said that the number of violations not wearing helmets in Tabanan Regency remains high, this reflects that the level of community awareness in Tabanan is still low. 2) The obstacles of the police in law enforcement against violations when dressed in Balinese custom are the lack of public awareness about understanding driving on the road, lack of facilities and infrastructure, lack of traffic police personnel.